Management of patent foramen ovale in embolic stroke of undetermined source patients: Malaysian experts' consensus - Albart, Stephenie Ann; Yusof Khan, Abdul Hanif Khan; Wan Zaidi, Wan Asyraf; Muthuppalaniappan, Annamalar Muthu; Kandavello, Geetha; Koh, Ghee Tiong; Leong, Ming Chern; Liew, Houng Bang; Ong, Beng Hooi; Viswanathan, Shanthi; Fan Kee, Hoo; Looi, Irene; et al. (Malaysia Medical Association, 2023)
Introduction: About 20 to 40 of ischaemic stroke causes are cryptogenic. Embolic stroke of undetermined source (ESUS) is a subtype of cryptogenic stroke which is diagnosed based on specific criteria. Even though patent foramen ovale (PFO) is linked with the risk of stroke, it is found in about 25 of the general population, so it might be an innocent bystander. The best way to treat ESUS patients with PFO is still up for discussion. Materials and Methods: Therefore, based on current evidence and expert opinion, Malaysian expert panels from various disciplines have gathered to discuss the management of ESUS patients with PFO. This consensus sought to educate Malaysian healthcare professionals to diagnose and manage PFO in ESUS patients based on local resources and facilities. Results: Based on consensus, the Malaysian expert recommended PFO closure for embolic stroke patients who were younger than 60, had high RoPE scores and did not require long-term anticoagulation. However, the decision should be made after other mechanisms of stroke have been ruled out via thorough investigation and multidisciplinary evaluation. The PFO screening should be made using readily available imaging modalities, ideally contrasttransthoracic echocardiogram (c-TTE) or contrasttranscranial Doppler (c-TCD). The contrast-transesophageal echocardiogram (c-TEE) should be used for the confirmation of PFO diagnosis. The experts advised closing PFO as early as possible because there is limited evidence for late closure. For the post-closure follow-up management, dual antiplatelet therapy (DAPT) for one to three months, followed by single antiplatelet therapy (APT) for six months, is advised. Nonetheless, with joint care from a cardiologist and a neurologist, the multidisciplinary team will decide on the continuation of therapy.